Phylogeny and taxonomic revision of the genus Craterispermum (Rubiaceae) in the Seychelles Archipelago - Padayachy, Tarah; de Block, Petra; Razafimandimbison, Sylvain G.; Taedoumg, Hermann; Baguette, François; Senterre, Bruno (Phytotaxa, 2020)
The genus Craterispermum (Craterispermeae, Rubiaceae) is distributed in the tropical rain forests of Africa and Madagascar, with one morphologically variable species (Craterispermum microdon) hitherto recognized in the Seychelles Archipelago. We conducted a Bayesian analysis of the combined ETS and ITS sequence data to: 1) test the monophyly of the Seychellois species of Craterispermum; and 2) assess the phylogenetic relationships between the island populations. Our analyses supported the monophyly and, therefore, the single Malagasy origin of the Seychellois Craterispermum. The phylogenetic relationships between the three island populations were unresolved, since the Seychellois plants display a very low level of molecular variation. However, both herbarium and field studies revealed that the Craterispermum taxa occurring on the islands of Mahé, Praslin, and Silhouette, are morphologically distinct and geographically separated. As a result of these studies, two new species, Craterispermum praslinense and C. silhouettense, are described, to accommodate the Praslin and Silhouette populations, respectively, and C. microdon is restricted to the population on Mahé Island. A new taxonomic account for the Seychellois Craterispermum, and an identification key to the three species present in the archipelago, are provided. A provisional conservation status of each species, according to the IUCN Categories and Criteria, is presented.